Ekonomiczne i finansowe aspekty rekreacyjnej i turystycznej funkcji lasu - Gołos, Piotr (Leśne Prace Badawcze, 2011)
In economic terms, an analysis of recreational goods and services provided by managed forests indicates that these can be defined as either pure or mixed public goods, as well as externalities and club goods. The provision of such a wide large diversity of goods and services makes it impossible to seek a single way of financing all the recreational benefits of managed forests from external (non-forestry) sources. For instance, in the case of public goods we must assume that only the state budget could co-fund their provision. Two out of the five proposed theoretical approaches to financing non-productive goods and services from forests may provide workable solutions to this funding problem. The first is the establishment of voluntary agreements between the entities managing forests and the traders whose business depends on the maintenance of their recreational function. In this case, the positions of the negotiating parties are unequal, as in Poland the law allows only those economic activities that do not threaten the sustainability of forests. The second potential solution is based on agreement between those entities managing forests and local governments. In practice, this could be achieved by the introduction of a levy, at the communal level, for ‘use’ of the forest. But the creation of new laws and working out technical details for such a solution are problematic, since they are related to, amongst other things, commune recreational valuation criteria, the value of the levy, as well as the methods of collecting payment and the appropriate end use to the funds generated.